PEMANFAATAN CRUMB RUBBER(TYRE RUBBER) SEBAGAI ADITIF PADA ASPAL MODIFIKASI POLIMER - Purnomo, Wahyu; Evaldo, Berry; Suparma, Latif Budi (FSTPT Indonesia, 2015)
Crumb rubber is a type of thermoplastic polymer, if mixed with asphalt has an advantage capable at high temperatures, heavy traffic, as well as more flexible. Asphalt mixture used in Indonesia in the form of hot mixture with dense graded, which is called asphalt concrete (laston / AC). Mixing asphalt with crumb rubber used high speed rotation method. Testing a mixture of pavement was conducted using Marshall Method. In this study, variation of crumb rubber as an asphalt additive modification used 5%, 10% and 12%. The test results demonstrate the increasing value of the properties of asphalt penetration, softening point, and viscosity which is the interpretation of high load traffic and high temperature. Marshall Test results showed that the polymer modified asphalt mixture with crumb rubber has a value of stability, flexibility and durability which is above the conventional mix. Based on this it is concluded that crumb rubber can be used as an additive polymer modified asphalt and asphalt mixture properties pavement better than conventional asphalt and mix. Optimum value which can be used in asphalt modification of the polymer is between 5% and 10%.